Influence Of Product Brand, Customer Satisfaction, Product Quality, Promotion, Service And Samsung Prices On Interest In Buying At Chandra's Shop Cellular Kotapinang - Lia Triana; Siti Lam'ah Nasution; Aziddin harahap (PT Mattawang Mediatama Solution, 2023)
This study aims to investigate the effect of Brand Product, Custemer Satisfaction Product Quality, Promotion, Service And Samsung Prices On Purchase Interest In Chandra Celluler Shops. Data collection was carried out by distributing questionnaires and distributing them to 100 research samples, namely Chandra cellular consumers. Data analysis in this study used SPSS version 20. Data testing techniques were carried out in partial and simultaneous testing. The results of the analysis show that overall the independent variables have a positive and significant influence on the dependent variable. This can be seen from the value of all t counts which have a value higher than 1.985 with a significant value below 0.05. Overall the final result of the study is that the independent variables provide influence of 0.906 or 90.06% and the rest is influenced by other supporting factors.